PATIENT-CENTERED OUTCOMES OF THERAPEUTIC STRATEGIES IN TREATMENT OF CHRONIC ULCERS - Iqra Suleman; Dr. Momina Tuz Zobia Malik; Dr. Syeda Shehar Bano; Dr. Atiqa Ali; Mehwish Idrees; Dr. Ayesha Iqbal Shehzad (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Chronic ulcers pose significant challenges in dermatological therapy. Understanding the etiology of these ulcers is pivotal for effective treatment. Local therapy is often indispensable, focusing on cleaning, debridement, infection control, and the application of various topical agents, including medications and dressings. Methods: This review explores recent therapeutic advancements for chronic ulcers, considering both established and emerging approaches. Results: A growing area of research focuses on the development and application of biological skin substitutes. These substitutes offer potential solutions for enhancing wound healing and tissue regeneration. Investigations into the role of growth factors in ulcer healing have shown promise. Identifying the most effective growth factors and methods for their delivery is essential to optimize treatment outcomes. Laser therapy is gaining attention as a viable option for ulcer management. Researchers are exploring the mechanisms and safety considerations associated with laser treatments for chronic ulcers. Hyperbaric oxygen therapy’s potential to expedite wound healing is under scrutiny. Determining optimal treatment protocols and understanding its influence on tissue regeneration are key areas of focus. Electrical stimulation has emerged as a potential adjunctive treatment for chronic ulcers. Investigating the mechanisms by which electrical stimulation promotes healing and its parameters for effective application is a critical research area. The use of negative pressure wound therapy is showing promise in ulcer management. Research efforts are directed towards understanding its mechanisms and identifying patient populations that benefit most from this therapy. Cost-Effectiveness Analysis: Evaluating the economic viability and accessibility of novel therapeutic strategies compared to traditional approaches is a vital component of current research. Patient-Centered Outcomes: Studies are assessing the impact of various ulcer treatments on patient quality of life, pain management, and overall well-being, considering patient-reported outcomes. Combination Therapies: Investigating the synergistic effects of combining multiple therapeutic strategies, such as growth factors with electrical stimulation or biological skin substitutes with hyperbaric oxygen therapy, is a significant area of inquiry. Conclusion: This comprehensive review of therapeutic advances in chronic ulcer management highlights the significance of ongoing research to improve treatment efficacy, patient outcomes, and the accessibility of innovative approaches. It also underscores the enduring value of traditional therapies.